The Ministry of Foreign Affairs Malaysia (MFA) HumanResource Development policy (HRD) : meeting thechallenge of the future ASEAN and global community / Mohd Yusof Ahmad - Ahmad, Mohd Yusof (Universiti Teknologi MARA, Shah Alam, 2009)
Although critics may disagree, Malaysia's past and current diplomatic engagements with ASEAN and the global community have indeed been remarkable. Despite the marked absence of a well thought out formal diplomatic training strategy at independence, Malaysia's first generation diplomats have indeed done a great job at helping to shape the content and direction of this successful endeavour. The resultant regional stability had not only helped Malaysia to pursue her development agenda in the region un-interrupted, but also earned her high respect not only among her regional neighbors but also the global community. Recent changes in the regional and global environment, increased competitiveness and globalization however, have brought in new challenges that could upset this positive scenario. The development requires new HRD approaches on the part of the Malaysian foreign ministry to ensure Malaysia's next generation diplomats are equipped with the right competencies to successfully manage these challenges. Despite recent initiatives to address the issue, the lack of medium to long term strategic focus, sustained commitment and other structural constraints could stymie the process and adversely affect Malaysia's future standing within the region and beyond. A serious reappraisal of the foreign ministry's current HRD template is therefore critical if Malaysia's diplomacy is to be in tune with the complex dynamics of the future ASEAN and global community.